THE ENGAGEMENT OF NON-DIGITAL LIBRARY RESOURCES AMONG UNDERGRADUATE STUDENTS OF SCHOOL OF INFORMATION SCIENCE, COLLEGE OF COMPUTING, INFORMATICS, AND MEDIA, UNIVERSITI TEKNOLOGI MARA (UITM) - Nurul Nur Fatihah Shapie; Nor Erlissa Abd Aziz; Mohamad Rahimi Mohamad Rosman (Journal of Islamic, Social, Economics and Development, 2023)
This research paper investigates the engagement of non-digital library resources among undergraduate students of School of Information Science, College of Computing, Informatics and Media, Universiti Teknologi Mara (UiTM). Information technology has changed the way of teaching and learning in higher learning institution that has make non-digital library resources are quickly becoming significant component. The objective of this study is to investigate on the engagement of non- digital library (non-DL) resources, along with its several factors of reliability, assurance, tangible, empathy, responsiveness, and level of satisfaction among the users that influence their engagement with non-DL resources based on the conceptual framework of SERVQUAL’s model. To achieve the objectives, a comprehensive literature review is conducted to identify relevant studies on the topic from various disciplines, including education, digital library, open access resources and technology, to gain a multidimensional understanding of the subject matter along with quantitative methodology of study to collect primary data. The finding of the study has unveiled substantial gaps in the existing literature regarding the lack of recent research on non-DL resources, especially in the aspect of engagement among the users. There is also noticeable gap in research pertaining to the reliability, quality, sustainability, and business models of non-DL resources. Further research is needed to explore the user’s engagement with non-DL resources using suitable model, thorough study to develop effective quality control measures, and publishing models, alongside with the effort to provide exhaustive information and awareness regarding copyright law and regulations in order to advance knowledge, inform practice, and give major positive impact to the field in the future.